The Giant Geriatric Syndromes Are Intensified by Diabetic Complications. (December 2018) - Lewandowicz, Andrzej; Skowronek, Paweł; Maksymiuk-Kłos, Agnieszka; Piątkiewicz, Paweł
By 2015, diabetes has affected more than 415 million people over the world. It is anticipated that 640 million adults will suffer from diabetes in 2040. The elongation of the life expectancy, as the result of better general health care, extends also the time when diabetic complications may develop together with other senility-specific problems. The Giant Geriatric Syndromes (Geriatric Giants) have been qualified by the original Nascher's criteria defined more than 100 years ago, but they are becoming more and more relevant in connection with the aging of societies. The criteria comprise the older age, commonness of the health problem, multifactorial etiology, functional or cognitive impairment, worsened outcome, and increased morbidity and mortality. We described the impact of diabetes on Geriatric Giants including cognitive dysfunction, depression, malnutrition, incontinence, falls and fractures, chronic pain, and the loss of senses. The association of diabetes with Geriatric Giants reveals as a vicious circle with the background of neurovascular complications. However, diabetes influence on the incidence of cancer in elderly was also discussed, since neoplastic diseases associate with Geriatric Giants, for example, chronic pain and depression. The knowledge about these aspects of functional decline in geriatric population is crucial to improve patient care.